2016
DOI: 10.1039/c5cp07558k
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast carrier dynamics of carbon nanodots in different pH environments

Abstract: Ultrafast carrier relaxation dynamics in fluorescent carbon nanodots is investigated by femtosecond transient absorption spectra at different pH environments so as to understand the mechanism of fluorescence for the first time. Utilizing multi-wavelength global analysis to fit the measured signal via a sequential model, four different relaxation channels are found, which are attributed to electron-electron scattering and surface state trapping, optical phonon scattering, acoustic phonon scattering and electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
55
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 45 publications
8
55
1
1
Order By: Relevance
“…[3] Thep hotophysical properties of the CD systems were investigated using transient absorption spectroscopy (TAS), [28] from femtosecond to second timescales in order to investigate intrinsic relaxation processes,t he nature of photogenerated species and charge transfer reactions.fs-TAS experiments revealed that photoexcitation of all CD types gave rise to atransient absorption signal spanning the visible range from 450-750 nm decaying on ap st imescale (Figure 3a,S23 and S24). [30,31] To simplify the comparison of complex decay traces (stretched exponentials on the fs-ns timescale ( Figure S26), biphasic behavior on the ms-s timescale), the decay kinetics were characterized by t 50 % .F rom fs-TAS measurements, t 50 % is on the order of af ew picoseconds (9 ps for g-N-CD, Figure 4) and does not show excitation fluence dependence ( Figure S27), indicating av ery fast geminate intrinsic relaxation process that outcompetes bimolecular reactions (100 ps assuming k diff = 1 10 10 m À1 s À1 and 1m of reactant). [9,29] It is possible that the shorter and longer wavelength features relate to core and surface states,r espectively,a sd etermined for graphene quantum dots.…”
mentioning
confidence: 99%
“…[3] Thep hotophysical properties of the CD systems were investigated using transient absorption spectroscopy (TAS), [28] from femtosecond to second timescales in order to investigate intrinsic relaxation processes,t he nature of photogenerated species and charge transfer reactions.fs-TAS experiments revealed that photoexcitation of all CD types gave rise to atransient absorption signal spanning the visible range from 450-750 nm decaying on ap st imescale (Figure 3a,S23 and S24). [30,31] To simplify the comparison of complex decay traces (stretched exponentials on the fs-ns timescale ( Figure S26), biphasic behavior on the ms-s timescale), the decay kinetics were characterized by t 50 % .F rom fs-TAS measurements, t 50 % is on the order of af ew picoseconds (9 ps for g-N-CD, Figure 4) and does not show excitation fluence dependence ( Figure S27), indicating av ery fast geminate intrinsic relaxation process that outcompetes bimolecular reactions (100 ps assuming k diff = 1 10 10 m À1 s À1 and 1m of reactant). [9,29] It is possible that the shorter and longer wavelength features relate to core and surface states,r espectively,a sd etermined for graphene quantum dots.…”
mentioning
confidence: 99%
“…Figures 2e,f show the TA spectra with different time delays, and kinetics of each featured wavelength in terms of delay time,respectively.T oexplore the detailed relaxation channels of the excited carriers,weused five exponent decay functions to globally fit the TA spectra. [13] To further investigate the piezochromic effect in Y-CDs, we investigated the influence of applied pressure on the luminescence of Y-CDs.E thanol was used as ap ressure transmitting medium (PTM). There are three characteristic regions:1 )the percentage of the fourth component is zero at both 500 and 610 nm;2 )the percentage of the first and fifth component is zero near 560 nm;3)the percentage of the fifth component is zero at 680 nm.…”
mentioning
confidence: 99%
“…Solutions were prepared with deionized water,a nd concentrations were kept at 0.1 mg mL À1 .T he CDs exhibit excitation-dependent emission spectra,t ypical for CDs, which peak in intensity for excitation at approximately 370 nm (seen also Figure S7 in the Supporting Information). [47][48][49] Ad irect comparison between F and the CD composition according to the XPS and NMR results showed ad irect correlation between the relative percentage ratio of C=O/ COOH groups and F,i ndicating that the emissive excited states in the CDs involveoxygen functional groups. [41] Significant differences were found: 1.82 %f or o-CDs, 1.28 %f or HTC-CDs, and 0.18 %f or r-CDs.…”
Section: Resultsmentioning
confidence: 99%